Analysis of using educational mobile application with augmented reality in asimilate knowledge of the surrounding world - Borek, Łukasz; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2016)
The paper presents research on the applying augmented reality technology in the process of knowledge assimilation by pupils. The study was conducted with the use of dedicated educational mobile application. The application takes the form of a quiz, where 3D objects represent answers. The aim of the analysis is to confirm the thesis that the augmented reality applied in mobile applications helps in learning new contents. Preliminary survey and the analysis of achieved users results confirmed the thesis.